2015
DOI: 10.1111/emr.12162
|View full text |Cite
|
Sign up to set email alerts
|

Lethal 1080 baiting continues to reduce European Red Fox (Vulpes vulpes) abundance after more than 25 years of continuous use in south‐west Western Australia

Abstract: Summary European Red Fox (Vulpes vulpes) baiting with 1080 poison (sodium fluoroacetate) is undertaken in many Australian sites to reduce fox abundance and to protect vulnerable native species from predation. The longest continuous use of fox baiting for fauna conservation commenced in south‐west Western Australia in the 1980s and includes baiting Dryandra Woodland and Tutanning Nature Reserve. The trap success of the Woylie (Bettongia penicillata) in these two reserves initially increased more than 20‐fold af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…2007; Moseby & Hill 2011; Marlow et al . 2015). Many practitioners measure baiting effectiveness through a reduction in the activity of the targeted predator species after baiting (Morris et al .…”
Section: Introductionmentioning
confidence: 99%
“…2007; Moseby & Hill 2011; Marlow et al . 2015). Many practitioners measure baiting effectiveness through a reduction in the activity of the targeted predator species after baiting (Morris et al .…”
Section: Introductionmentioning
confidence: 99%
“…Cage and field-based (Ogilvie et al 1996) studies show that altering the bait matrix can partially overcome aversive behaviour. Marlow et al (2015) found that changing from dried meat baits to Probait Ò increased uptake by foxes in two Western Australian reserves. Switching between a cereal bait and gel increased efficacy in common brushtail possums (Ross et al 2000).…”
Section: Variation In Bait Presentation and Toxinmentioning
confidence: 99%
“…Broad‐scale baiting occurs regularly in Australia to control invasive pests for biodiversity conservation and land management, and to reduce losses to agriculture (Marlow et al . ). Successful bait uptake is reliant upon the target species locating the bait, consuming the bait and thereby ingesting a lethal dose of the toxin.…”
Section: Introductionmentioning
confidence: 97%